Aqueous‐Phase Amination of Biogenic Isohexides by using Ru/C as a Solid Catalyst. Issue 1 (26th November 2015) - Pfützenreuter, Rebecca; Rose, Marcus
Abstract: An aqueous phase process for the amination of biogenic isohexides with ammonia using Ru/C as solid catalyst is reported. The products possess great potential for the production of biogenic polyamides. From the diol substrates amino alcohols and diamines are derived as main products with significantly varying product selectivity depending on the substrates' stereochemistry. The catalytic reaction is performed at temperatures of 140–180 °C. The Ru/C catalyst shows a high activity in the aqueous phase, which is beneficial for the transformation of the polar biogenic substrates. Despite the basic conditions, the metal leaching is negligible and the catalyst can be recycled easily in batch operation and, thus, enables further process development thanks to the mild and scalable reaction conditions. Abstract : Hydrophilic reaction : Biogenic isohexides can be converted to their amine derivatives by a catalytic aqueous‐phase amination reaction. The solid catalyst Ru/C proves to be highly active and shows only negligible metal leaching. Depending on the stereochemistry of the substrate, an unexpected product selectivity is observed.